Kiribati : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Kiribati's key economic challenges are to reduce large structural fiscal imbalances and increase growth and employment opportunities, while facing obstacles posed by remoteness, lack of scale, vulnerabilities to external shocks and climate change. The significant fiscal consolidation envisaged by the authorities will help stabilize Kiribati's sovereign wealth fund (the Revenue Equalization Reserve Fund, or RERF) in real per capita terms. This stabilization effort would also require that fishing license fees remain close to recent exceptionally high levels, with windfall incomes relative to the conservative budgeted baseline saved. In the event of weaker fishing license fee revenues, a more ambitious adjustment in the non-fishing budget would be needed. The small private sector share in the economy due to remoteness and weaknesses in business climate constrains growth and puts strain on public finances. Continuing the fiscal and structural reform program is essential. Climate change brings additional risks and fiscal costs. Main Recommendations: -- Continue fiscal reforms designed to deliver fiscal consolidation and improved public financial management. Seek to maintain fishing license fees above the current conservative budget baseline, with windfalls saved to strengthen RERF balances. If fishing license fee windfalls cannot be sustained, explore other options to further strengthen fiscal balances. -- Continue reforms of state-owned enterprises (SOEs). -- Facilitate growth through improving the business climate and infrastructure, including through streamlining government services.